RANCANG BANGUN SISTEM MONITORING PERTUMBUHAN BERAT DAN TINGGI ANAK BALITA BERBASIS DATA PADA POSYANDU - Sardi, Juli; Habibullah, Habibullah; Risfendra, Risfendra (ELKHA : Jurnal Teknik Elektro, 2019)
Abstract – Posyandu (Integrated Service Post) is one form of health services in Indonesia that is based on community resources, especially for the health of mothers and balita (children under five). One of the services at the Posyandu is monitoring the growth of balita by measuring their weight and height regularly. So far, the measuring instrument used conventional and the results are not stored properly. This study aims to apply the database that are integrated with measuring instruments that can be used to monitor the growth of balita. The proposed system includes making a measuring device (hardware) that is connected to a database application (software). Hardware includes loadcell circuits, ultrasonic sensors and Arduino as data processors. LabView is used for database applications and interfaces. The system has the function of data acquisition, monitoring, storing data into a database, displaying and printing data. The results show all aforementioned functions are successfully working to achieve the design requirements. This application can be used to monitor the growth of balita at the Posyandu. The measurement data is stored for database. Recapitulation of measurement result can be displayed in graphical and can be directly printed to be given to parents of balita when measuring their children.